Customer motivation towards salary deduction scheme: a case study of Amanah Saham Bumiputera (ASB) Scheme / Shareena Adnan - Adnan, Shareena (Faculty of Business and Management, 2007)
ASNS has offered 10 types of schemes, which are ASN, ASN 2, ASN 3, ASG-Pendidikan, ASG-Kesihatan, ASG-Persaraan, ASS, ASW 2020, ASM, and ASD. Salary deduction scheme is offer to those who are working and have fixed salary. This salary deduction scheme is meant for ASS unit holder. The investors can deposit a minimum amount of RM10 of their salary into their account every month. But, there are some problems in terms of investors motivation towards the scheme In this context, this study mainly focuses on the customer's motivation towards salary deduction scheme. Moreover, this study seeks to know about the investors' savings motivator, motives behind savings withdrawal and the extent of acceptance towards communicated information regarding salary deduction scheme. In the first objective, the analysis shows that most of the investors agreed the main subscription motives in salary deduction scheme is because of investment purpose. For the second objective, the main reason of withdrawing is because of insufficient for other expenditure such as children education, daily expenditure etc. In the analysis for the third objective, most of the investors are satisfied with media used, the completeness and accuracy of the information